2014
DOI: 10.1017/s0029665114000639
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the microbiota in inflammatory bowel diseases: prebiotics, probiotics or faecal transplantation?

Abstract: Crohn's disease (CD) and ulcerative colitis (UC) are the two major phenotypes of inflammatory bowel diseases (IBD) which constitute a spectrum of chronic, debilitating diseases characterised by a relapsing inflammation of the intestinal mucosal lining. Evidence from a variety of disciplines implicates the intestinal microbiota in the pathogenesis of idiopathic IBD and their complications, including pouchitis. Many studies have reported a dysbiosis in IBD, characterised by a decrease in diversity, a decreased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 103 publications
0
18
0
1
Order By: Relevance
“…It has been hypothesized that the beneficial activities might include altering the composition of the microbiota by competition for adhesion sites and nutrients or by secretion of bacteriocins and lactic acids, enhancement of intestinal barrier function (via increased production of mucus and anti-microbial peptides by epithelia), and modulation of immune cell responses. 35,36 There are only few reports on the use of probiotic bacteria in dogs with gastroenteritis. Earlier in vitro studies have confirmed the ability of a lyophilized probiotic cocktail (e.g., 3 different Lactobacillus spp strains) to modulate the expression of regulatory vs. pro-inflammatory cytokines in dogs with chronic enteropathies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that the beneficial activities might include altering the composition of the microbiota by competition for adhesion sites and nutrients or by secretion of bacteriocins and lactic acids, enhancement of intestinal barrier function (via increased production of mucus and anti-microbial peptides by epithelia), and modulation of immune cell responses. 35,36 There are only few reports on the use of probiotic bacteria in dogs with gastroenteritis. Earlier in vitro studies have confirmed the ability of a lyophilized probiotic cocktail (e.g., 3 different Lactobacillus spp strains) to modulate the expression of regulatory vs. pro-inflammatory cytokines in dogs with chronic enteropathies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, butyrate is the primary metabolic fuel for distal colonic epithelial cells. Multiple studies demonstrate efficacy of oral prebiotics, either alone or in combination with probiotics (synbiotics) in experimental colitis [90], but proof of efficacy in human CD in UC patients is still limited [23,90,91]. A controlled four-week trial of fructo-oligosaccharides demonstrated no effect on remission rates in patients with active CD [92].…”
Section: Prebioticsmentioning
confidence: 99%
“…Observational studies of dysbiosis in IBD [127] and the disparities in host-microbe relationships which play part to the extent, severity, and chronicity of intestinal inflammation led to efforts to restore microbiota to a normal composition [128]. Further, a successful novel management approach in patients suffering from IBD using fecal microbial transplantation (FMT) has been introduced [129,130]. One randomized control trial involving 75 UC cases demonstrated a significantly escalated remission rate (24%) in individuals cases treated with FMT from unrelated/discrete donor enemas than that in the placebo array (5%) [131].…”
Section: Clostridiummentioning
confidence: 99%